Efektivitas Metode Quantum Learning dalam Mengajarkan Al-Qur'an dan Hadits kepada Murid SDN 249/Vi Rawa Jaya - Anwar, Ahmad; Mazidah, Umi; Hartatik, Hartatik (TSAQOFAH, 2025)
This study aims to analyze the effectiveness of the Quantum Learning method in teaching Al-Qur'an and Hadith at SDN 249/VI Rawa Jaya. The background of this research lies in the need for innovation in Islamic education to improve students' understanding, motivation, and engagement. Quantum Learning offers an interactive, creative, and enjoyable approach, making it relevant to address challenges in conventional learning, such as low student interest and difficulties in understanding the material. The study uses a quantitative descriptive method with a quasi-experimental design approach. The research subjects were students of SDN 249/VI Rawa Jaya selected purposively. Data was collected through learning outcome tests, questionnaires, observations, and documentation. A pre-test was conducted to measure students' initial abilities, while a post-test assessed the effectiveness of the Quantum Learning method. Questionnaires were distributed to gather students’ responses to the method, while observations recorded students’ activities and engagement during the learning process. The results showed a significant improvement in students' post-test scores after implementing the Quantum Learning method. The average scores of students increased significantly compared to their pre-test results. Moreover, students responded positively to the method, expressing that the learning process became more engaging, easier to understand, and enjoyable. Observations revealed that the method successfully created an interactive learning environment, where students actively participated in group discussions, educational games, and visually-based activities. Inferential analysis using the t-test demonstrated that the Quantum Learning method had a significant impact on students’ learning outcomes. The method not only enhanced students' cognitive understanding but also positively influenced their affective aspects, such as motivation and confidence in studying Al-Qur'an and Hadith. In conclusion, the Quantum Learning method is proven effective in improving students’ learning outcomes at SDN 249/VI Rawa Jaya. However, the study identified some challenges, such as limited time and the need for teacher training to optimize the method. It is recommended that schools support the implementation of this method by allocating sufficient time, providing teacher training, and developing adequate learning facilities. This research is expected to serve as a reference for developing more effective and innovative Islamic education methods at the elementary school level.